THE EFFECT ON OVERCOMING MISCONCEPTIONS OF COMPUTER ASSISTED INSTRUCTION IN TEACHING SOCIAL STUDIES - Erkan YEŞİLTAŞ (Fırat University, 2019)
The concept is a term of the common features of objects and events and can describe them in general terms together under a common name in its simplest expression about threads associate with short syntax. Misconceptions are the concept of the in